Sikap Toleransi Dan Empati Remaja Pra Nikah Terhadap Penganut Childfree - Wulan Mujiawati; Ratnaningrum ZD; Masnia Ningsih (Institut Nalanda, 2024)
The decision not to have children, known as childfree, is a conscious choice made by a married couple. Childfree has become a hot topic of discussion among young Indonesians, especially on social media. This study aims to identify and analyze the level of tolerance and empathy possessed by pre-married adolescents towards individuals who choose not to have children (childfree). This study uses a descriptive qualitative approach, using five male adolescent informants aged 23-24 years from various academic backgrounds as subjects. The selection of informants with different backgrounds aims to obtain more diverse views on attitudes towards childfree. The results of the study show that most informants show a tolerant attitude towards the childfree decision. This attitude of tolerance is shown through respect for other people's life choices, without any tendency to judge or reject the choice.